Cover Picture: High‐Resolution 3D Proton MRI of Hyperpolarized Gas Enabled by Parahydrogen and Rh/TiO2 Heterogeneous Catalyst (Chem. Eur. J. 37/2014). Issue 37 (8th September 2014) - Kovtunov, Kirill V.; Barskiy, Danila A.; Coffey, Aaron M.; Truong, Milton L.; Salnikov, Oleg G.; Khudorozhkov, Alexander K.; Inozemtseva, Elizaveta A.; Prosvirin, Igor P.; Bukhtiyarov, Valery I.; Waddell, Kevin W.; Chekmenev, Eduard Y.; Koptyug, Igor V.
<x xml:space="preserve">Abstract</x> Preclinical and clinical imaging of porous media or void spaces such as human lungs could be possible. In their Communication on page 11636 ff., K. Kovtunov, E. Chekmenev et al. describe the 3D 1H MRI of hyperpolarized flowing propane at relatively short times with microscale spatial resolution and a large imaging matrix. The hyperpolarized propane was prepared by using a Rh/TiO2 catalyst with Rh particle size of 1.6 nm. This highly stable catalyst allows for preparation of nontoxic asphyxiant hyperpolarized propane gas to potentially enable robust preclinical and clinical 3D molecular imaging.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>